(untitled) (Journal of Computational Mathematics, 2004)
Properties of symplectic Runge-Kutta (RK) methods and symplectic partitioned Runge- Kutta (PRK) methods with real eigenvalues are discussed in this paper. It is shown that an s stage such method can't reach order more than s + 1. Particularly, we prove that no symplectic RK method with real eigenvalues exists in stage s of order s + 1 when s is even. But an example constructed by using the W-transformation shows that PRK method of this type does not necessarily meet this order barrier. Another useful way other than W-transformation to construct symplectic PRK method with real eigenvalues is then presented. Finally, a class of efficient symplectic methods is recommended.